Gamification-based tele-rehabilitation for physical therapy in patients with Parkinson’s disease: A scoping review - Somayeh Norouzi-Ghazbi; Shaghayegh Mirbaha; Zoe Li; Jan Andrysek; Roger Goldstein; Sander L. Hitzig (PLoS ONE, 2025)
Objective A scoping review was conducted to explore what is known about gamification-based tele-rehabilitation (GBT) to enable physical therapy in home settings for people with Parkinson’s disease (PD). Methods The peer-reviewed literature (OVID Medline, OVID EMBASE, CINAHL EBSCO, and Scopus databases) was searched from January 2010 to May 2024, and 24 articles met the inclusion criteria. The methodological quality of the studies was assessed using the Downs and Black evaluation tool, and levels of evidence were assigned using a modified Sackett scale. Results The majority of the 24 studies were of poor to fair methodological quality (83%), and all used a quantitative design with small sample sizes. The focus of the included studies was to enhance whole-body rehabilitation, with most addressing the upper extremities. Thirteen studies customized their games, whereas others utilized strictly commercial systems (n = 11). Eight studies reported no adverse events while the rest did not report on these. Eight studies indicated that participants maintained high levels of motivation and adherence in home settings. Conclusion GBT has the potential to offer a safe, engaging and effective physical therapy to the PD population in home settings, but further research is warranted to help delineate clearer implementation considerations.